Transgressive a trans woman on gender, feminism and politics - Williams, Rachel Anne 1988- (Jessica Kingsley Publishers, 2019)
"How do I know I am trans? Is trans feminism real feminism? What is there to say about trans women's male privilege? This collection of insightful, pithy and passionately argued think pieces from a trans-feminist perspective explores issues surrounding gender, feminism and philosophy and challenges misconceptions about trans identities. The book confronts contentious debates in gender studies to alleviate ongoing tension between feminism and trans women. Split into six sections, this collection covers wider issues, as well as autobiographical experiences, designed to stimulate the reader and encourage them to actively participate"--